Glycosyltransferase genes that cause monogenic congenital disorders of glycosylation are distinct from glycosyltransferase genes associated with complex diseases. (22nd March 2018) - Joshi, Hiren J; Hansen, Lars; Narimatsu, Yoshiki; Freeze, Hudson H; Henrissat, Bernard; Bennett, Eric; Wandall, Hans H; Clausen, Henrik; Schjoldager, Katrine T
Abstract: Glycosylation of proteins, lipids and proteoglycans in human cells involves at least 167 identified glycosyltransferases (GTfs), and these orchestrate the biosynthesis of diverse types of glycoconjugates and glycan structures. Mutations in this part of the genome—the GTf-genome—cause more than 58 rare, monogenic congenital disorders of glycosylation (CDGs). They are also statistically associated with a large number of complex phenotypes, diseases or predispositions to complex diseases based on Genome-Wide Association Studies (GWAS). CDGs are extremely rare and often with severe medical consequences. In contrast, GWAS are likely to identify more common genetic variations and generally involve less severe and distinct traits. We recently confirmed that structural defects in GTf genes are extremely rare, which seemed at odds with the large number of GWAS pointing to GTf-genes. To resolve this issue, we surveyed the GTf-genome for reported CDGs and GWAS candidates; we found little overlap between the two groups of genes. Moreover, GTf-genes implicated by CDG or GWAS appear to constitute different classes with respect to their: (i) predicted roles in glycosylation pathways; (ii) potential for partial redundancy by closely homologous genes; and (iii) transcriptional regulation as evaluated by RNAseq data. Our analysis suggest that more complex traits are caused by dysregulation rather than structural deficiency of GTfs, which suggests that some glycosylation reactions may be predicted to be under tight regulation for fine-tuning of important biological functions.